2008
DOI: 10.1212/01.wnl.0000284604.61160.2d
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled trial of repeated IV antibiotic therapy for Lyme encephalopathy

Abstract: IV ceftriaxone therapy results in short-term cognitive improvement for patients with posttreatment Lyme encephalopathy, but relapse in cognition occurs after the antibiotic is discontinued. Treatment strategies that result in sustained cognitive improvement are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
372
2
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(397 citation statements)
references
References 33 publications
(26 reference statements)
12
372
2
11
Order By: Relevance
“…Patients in Category 2 have other recognized diseases and have been misdiagnosed with Lyme disease. The distribution of patients who fall into these categories can be estimated by the difficulty in accruing patients into the placebo-controlled studies of antibiotic treatment in patients with post-Lyme disease syndrome (Category 4), where only 1 to 10% of the screened individuals were eligible [2][3][4].…”
Section: Chronic Lyme Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Patients in Category 2 have other recognized diseases and have been misdiagnosed with Lyme disease. The distribution of patients who fall into these categories can be estimated by the difficulty in accruing patients into the placebo-controlled studies of antibiotic treatment in patients with post-Lyme disease syndrome (Category 4), where only 1 to 10% of the screened individuals were eligible [2][3][4].…”
Section: Chronic Lyme Diseasementioning
confidence: 99%
“…Recent studies showed little evidence of a substantial role of other tick-borne infections in the majority of patients with post-Lyme disease syndrome [4,[48][49][50]. There has been little research in the role of autoimmunity in post-Lyme disease syndrome, but one study showed no association between a class II allele or genotype [51].…”
Section: The Possible Causes Of Post-lyme Disease Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of antibiotics in combination with corticosteroids facilitates healing, but corticosteroidsdo not have noticeable effect on motor deficit. In randomized clinical trials no differences were observed among Penicillin G administered in high doses, Ceftriaxone, Cefotaxime and Doxycycline [44].…”
Section: Treatment Of Lyme Neuroborreliosismentioning
confidence: 92%